As I Remember: Vard M. Shepard (1967)
George P. Cooper's interview with Vard M. Shepard, a former faculty member and dean of the Agriculture Department at Cal Poly from 1947 to 1961. [00:00:05] As I Remember Opening [00:00:20] Shepard describes how he heard about and came to Cal Poly [00:01:16] Shepard describes why he left high school teaching [00:01:44] Shepard describes speaking with J.I. Tomson concerning the service area of Cal Poly and creating a center for the future farmers [00:02:44] Shepard describes enrollment in the agriculture program at the time he first came to Cal Poly in 1932 [00:03:11] Shepard discusses the number of students in the animal husbandry program [00:03:28] Shepard describes the facilities that were around when he first came to Cal Poly [00:04:17] Shepard discusses the steps he took to improve student enrollment, curriculum, and student facilities [00:05:48] Shepard discusses the level of student instruction when he first came to Cal Poly [00:06:41] Shepard discusses taking animals to the fair and competing [00:08:26] Shepard recalls a time when he had a shipping problem when he was heading to Junior Livestock Show [00:09:34] Shepard discusses progress in building and increasing student enrollment in 1932-1937 [00:10:33] Shepard discusses working in stock yards in 1937 [00:11:19] Shepard discusses working as a livestock specialist [00:11:44] Shepard discusses how the war affected his career plans [00:12:28] Shepard discusses laborers in agriculture [00:12:53] Shepard discusses the development of and reasons for grading herds [00:14:05] Shepard discusses speaking with McPhee about returning to Cal Poly [00:14:34] Shepard discusses the incentive to return to Cal Poly and his new role as Dean of Agriculture [00:14:56] Shepard describes the changes that had taken place while he was away from Cal Poly for 10 years [00:15:37] Shepard describes the increased maturity of returning students [00:15:59] Shepard describes the expansion of Cal Poly's agriculture program [00:16:56] Shepard discusses the specialty program involved with the horse industry, scholarships, and the success of the program [00:18:10] Shepard discusses the addition of new buildings as part of the Master Plan [00:19:03] Shepard discusses the expansion of the area designated for range cattle [00:20:16] Shepard describes the development of Cal Poly's training in meats program [00:22:24] Shepard describes the development of the commercial feed mill [00:23:14] Shepard talks about an international student in the program and international students at Cal Poly [00:25:26] Shepard discusses Cal Poly's agricultural program's international reputation [00:27:04] Shepard discussion changes in the agricultural curriculum from straight production to one embodying related fields [00:28:23] Shepard recalls times when faculty members gathered firewood for the coming winter [00:29:38] Shepard describes his time working in Egypt as an agricultural officer [00:30:50] Shepard describes the other countries he visited while in the Middle East [00:31:23] Shepard discusses progress he made while working overseas [00:32:04] Shepard discusses his experience in working in Guatemala for a year [00:34:05] Shepard talks about his loyalty to Cal Poly [00:35:01] "As I Remember" Closing